Graphene field effect transistor as radiation sensor - Patil, A.; Koybasi, O.; Lopez, G.; Foxe, M.; Childres, I.; Roecker, C.; Boguski, J.; Gu, J.; Bolen, M. L.; Capano, M. A.; Jovanovic, I.; Ye, P.; et al. (2011 IEEE Nuclear Science Symposium Conference Record, 2011)
A novel radiation sensor based on a graphene field effect transistor (GFET) is experimentally demonstrated. The detection relies on the high sensitivity of the resistivity of graphene to the local change of electric field that can result from ionized charges produced in the underlying semiconductor substrate. We present the experimental results of our study on the response of graphene-based radiation detectors to X-rays, gamma-rays, and light photons. We observed increasing resistance change of graphene with increasing X-ray flux in an electrically biased GFET based on Si, SiC, and GaAs substrates. We have measured the temporal characteristics of our detector, along with the sensitivity of the device at high (40 keV, 80 μA) and low (15 keV, 15 μA) X-ray fluxes. Furthermore, we demonstrate room-temperature operation of a GFET based on a SiC absorber and explore new architecture for a faster response.